Effect of the Symbolic Meaning of Speed on the Perceived Duration of Children and Adults - Mioni, Giovanna; Stablum, Franca; Grondin, Simon; Altoé, Gianmarco; Zakay, Dan (Frontiers in Psychology, 2018)
The present study investigated how the symbolic meaning of speed affects time perception in children and adults. We employed a time reproduction task in which participants were asked to reproduce temporal intervals previously presented. In Experiment 1, 45 primary school children and 22 university students performed a time reproduction task with cars (meaning of fastness) and trucks (meaning of slowness) presented for 11 and 21 sec in static and moving conditions. Results showed that young children under-reproduced the duration more than the older children and adults, especially when the stimulus presented was a car. Moreover, participants under-reproduced moving stimuli compared to static one. In Experiment 2, we tested 289 participants who were divided into 9 different age groups according to their school class: 5 from primary school, 3 from Junior High and one from the university. Participants performed a time reproduction task with a motorbike (meaning of fastness) or a bicycle (meaning of slowness) under static and moving conditions for 11, 21 and 36 sec. The results confirmed the effects of symbolic meaning of speed on children’s time perception and showed that vehicles that evoked the idea of fastness were under-reproduced compared to stimuli evoking the idea of slowness.